TEMPERAMENT AND ILLNESS (Spectrum Journal of Innovation, Reforms and Development, 2023)
This article delves into the intricate relationship between temperament and illness, seeking to unravel the potential links and implications that exist between an individual's inherent disposition and their susceptibility to various health conditions. Through a comprehensive literature analysis, we aim to shed light on the existing knowledge in this domain, followed by a discussion on potential methods for further exploration. The findings from this research may contribute to a better understanding of the psychophysiological factors influencing health outcomes.